Role of calcium dioleate in the flotation of powellite particles using oleate. (July 2019) - Wang, Zhen; Wang, Li; Zheng, Yongxing; Xiao, Junhui
Graphical abstract: The interaction distance of the two molecules with Ca active sites are 4.147 Å and 4.124 Å, respectively, while hydrogen bond length between the hydrogen atom of Ca(Ol)2 and oxygen atom of powellite (1 1 1) surface is 1.887 Å, which are consistent with the difference in adsorption energies and flotation performance. Highlights: Washed powellite (W-M) floats better with Ca 2+ /Ol − than with Ol − . Ca(Ol)2 are predominantly responsible for powellite (R-M) flotation with Ol − . Recovery: R-M/Ol − > W-M/Ca 2+  + Ol − > W-M/Ol − > W-M > W-M/Ca 2+ > R-M. Most hydrophobic surface from R-M/Ol −, W-M/Ca 2+  + Ol − second best. Abstract: Micro-flotation, zeta potential, fluorescence emission, interface topography and XPS tests were carried out to investigate the flotation and adsorption of sodium oleate (NaOl) on powellite. Micro-flotation results show that the flotation recovery varies with different Ca 2+ concentrations in pulps. The greater negative charge on the washed powellite (W-M) surface with both Ca 2+ and Ol − compared to that with only Ol − could be explained by the additional adsorption of Ol − on the surface, along with calcium dioleate precipitation through hydrophobic interactions between hydrocarbon chains in the Ol − ion and Ca(Ol)2, as indicated by the results from zeta potential measurements. The most nonpolar powellite surface were obtained from raw powellite (R-M) with Ol − and washed powellite with both Ca 2+ and Ol −, which is in good accordance with flotation and zeta potential test results. When the powellite crystal was equilibrated with a mixed solution of calcium chloride and sodium oleate, the surface roughness average increased greatly from 4.503 nm to 16.327 nm, revealing the formation of non-uniform clusters of Ca(Ol)2 precipitates. XPS analysis further demonstrates the release of Ca ions into powellite pulp and the removal of them by ultrasonic treatment. The adsorption of Ca(Ol)2 and oleate anions are responsible for the flotation of powellite using NaOl, and the former is more predominant. A suggested comparative model are given through molecular dynamics simulation analysis.